2005
DOI: 10.1348/096317905x40097
|View full text |Cite
|
Sign up to set email alerts
|

Extending the demands‐control model: A daily diary study of job characteristics, work‐family conflict and work‐family facilitation

Abstract: Using personal digital assistants, 91 parents employed in non-professional occupations were surveyed for 14 consecutive days about their job characteristics and work-family experiences. We found significant daily variation in work-to-family conflict (WFC) and work-to-family facilitation (WFF) that was predictable from daily job characteristics. Higher levels of WFC were associated with greater job demands and control at work. Contrary to the demands-control model (Karasek, 1979), these two job characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
204
3
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(237 citation statements)
references
References 44 publications
18
204
3
6
Order By: Relevance
“…Previous studies have indicated that high job demands 10,[14][15][16] and low job control 14,16,17) are positively associated with WFC, which are individual job characteristics in the job-demand-control model 18) . Work-family culture has been found to be negatively associated with WFC 19,20) .…”
Section: Relationship Between Work-related Factors and Wfcmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that high job demands 10,[14][15][16] and low job control 14,16,17) are positively associated with WFC, which are individual job characteristics in the job-demand-control model 18) . Work-family culture has been found to be negatively associated with WFC 19,20) .…”
Section: Relationship Between Work-related Factors and Wfcmentioning
confidence: 99%
“…Several longitudinal studies have consistently reported health consequences of work-family conflict, including depression 26,27) as a mental health indicator and fatigue 14,15,27) as a physical health indicator. Although family-related variables generally have been used as outcomes of work-family conflict 28) , to our knowledge, there have been no studies that have explicitly addressed the issue of what role family togetherness plays in the path between WFC and health.…”
Section: Relationship Between Wfc and Health And Familymentioning
confidence: 99%
“…Short term variations in job characteristics have also been associated with fluctuations in employee outcomes including work engagement, work-family facilitation and work-family conflict (Butler, Grzywacz, Bass & Linney, 2005;Petrou et al, 2012). Despite this, previous studies addressing the well-being implications of lean manufacturing for employees (including Study 2 in this thesis) have exclusively focused on relationships at the between-person level, where job characteristics and employee outcomes are considered to be relatively stable (e.g.…”
Section: Theory Expansionmentioning
confidence: 99%
“…The higher the family participation was, the worse they performed at university (Meeuwisse, et al, 2011) the more conflict they experienced between their family lives and their lives as students, because time spent on family activities cannot be devoted to studying (Meeuwisse, et al, 2011;Greenhaus & Beutell, 1985). As time with family or work hours were determined as an antecedent of conflict (Butler, et al, 2005;Ford, et al, 2007), and multiple roles may compete for a person's time (Greenhaus & Beutell, 1985). For example, household duties such as housework and childcare-related obligations are factors that can create time-based pressure from the family realm (Baltes & Heydens-Gahir, 2003;Frone, et al, 1992).…”
Section: Familymentioning
confidence: 99%